Housing finance and monetary policy - Alessandro Calza; Livio Stracca; Tommaso Monacelli (European Central Bank (ECB), 2009)
We study how the structure of housing finance affects the transmission of monetary policy shocks. We document three main facts: first, the features of residential mortgage markets differ markedly across industrialized countries; second, and ac- cording to a wide range of indicators, the transmission of monetary policy shocks to residential investment and house prices is significantly stronger in those countries with larger flexibility/development of mortgage markets; third, the transmission to consumption is stronger only in those countries where mortgage equity release is common and mortgage contracts are predominantly of the variable-rate type. We build a two-sector DSGE model with price stickiness and collateral constraints and analyze how the response of consumption and residential investment to monetary policy shocks is affected by alternative values of two institutional features: (i) down-payment rate; (ii) interest rate mortgage structure (variable vs. fixed rate). In line with our empirical evidence, the sensitivity of both variables to monetary policy shocks increases with lower values of the down-payment rate and is larger under a variable-rate mortgage structure.
Keywords: E21; E44; E52; 330; collateral constraint; Housing finance; monetary policy; Mortgage markets; Immobilienfinanzierung; Hypothekenbank; Zinsstruktur; Immobilienpreis; Geldpolitik; Geldpolitische Transmission; OECD-Staaten